Penomoran dan Penanggalan Akta Notaris Berdasarkan Putusan Pengadilan (Analisis Putusan PN Denpasar Nomor 530/Pdt. G/2016/PN. Dps.) - Istadevi Utami Rahardika; I Nyoman Gede Sugiartha; Putu Ayu Sriasih Wesna (Jurnal Interpretasi Hukum, 2021)
The Denpasar District Court (PN) in its decision Number 530 / Pdt.G / 2016 / PN.Dps stated that it has punished the Notary to immediately give the number and date to the Sale and Purchase Binding Agreement Deed and the Power of Attorney. This is interesting and important to examine in this research in relation to the basis of authority and the method of assigning the number and date of the deed signed by the parties before the notary after the Denpasar District Court decision. This normative legal research aims to examine the contents of a positive legal level, concerning the Numbering and Dating of Notary Deeds, using primary, secondary and tertiary legal materials, while the analysis method uses grammatical and systematic interpretation. The results showed that the basic authority of the Denpasar District Court to decide disputes regarding the numbering and dating of notary deeds, namely Article 130 HIR / 154 Rbg, Article 1851 of the Civil Code, Law of the Republic of Indonesia Number 48 of 2009, Perma RI Number 1 of 2016, and the principle of ius curia novit. In connection with the numbering and dating of the Notary deed, it can be done based on the provisions of the UUJNP and refers to the Denpasar District Court decision.